CT perfusion and EEG patterns in patients with acute isolated aphasia in seizure-related stroke mimics. (October 2019) - Manganotti, Paolo; Furlanis, Giovanni; Ajčević, Miloš; Polverino, Paola; Caruso, Paola; Ridolfi, Mariana; Pozzi-Mucelli, Roberta Antea; Cova, Maria Assunta; Naccarato, Marcello
Highlights: Acute isolated aphasia is a challenging symptom for etiopathogenic diagnosis. Seizure-related isolated aphasia presents hyperperfusion on CTP and sharp EEG waves. CTP/EEG may improve diagnosis of ischemic/epileptic-related isolated aphasia. Abstract: Purpose: Isolated speech impairment is one of the most challenging clinical manifestations of stroke mimic (SM). We aimed to investigate perfusional and EEG pattern of isolated aphasia to better differentiate between vascular and epileptic etiology in emergency settings. Method: We retrospectively analyzed 481 cases with acute focal neurological symptoms admitted to our Stroke Unit. The patients showing isolated aphasia and confirmed ischemic infarction or SM with seizure etiology on follow-up were included for subsequent analysis of clinical, neuroimaging, and EEG data. We investigated differences in CT Perfusion maps between ROI in the anatomical area compatible with clinical presentation, contralateral ROI and EEG in order to evaluate perfusion and brain oscillatory activity abnormalities. Results: 45 patients presented isolated aphasia as principal neurological symptom: 27 cases due to acute ischemic event, 11 due to seizure SM, while 7 were SM due to other etiologies. Out of 11 SM patients with seizure etiology, significant hyperperfusion on CTP maps (MTT AI%<-10%) and sharp EEG waves were observed in 8 patients, while in 3 patients slight hypoperfusion (MTT AI%<20%) and slow EEG rhythms were detected. 24 out of 27 ischemic stroke patients presented severe hypoperfusion with MTT AI above the stroke threshold (MTT AI > 45%). All ischemic stroke patients presented slower EEG rhythms. Conclusions: The main finding of this study is the identification of different clinical and neuroimaging patterns of isolated aphasia with epileptic or ischemic etiology in emergency settings.